2002
DOI: 10.1007/s710-002-8217-3
|View full text |Cite
|
Sign up to set email alerts
|

The role of apatite fractionation and REE distribution in alkaline rocks from Mt. Etna, Sicily

Abstract: Melt inclusions in olivine and apatite, and REE distribution of apatite were studied in one of the least differentiated members of the oldest alkaline succession of Mt. Etna. Apatite occurs both as microphenocrysts and as inclusions in olivine crystals, even in the most Mg-rich ones (Fo 82 ). In addition phenocrysts and groundmass are composed of plagioclase, clinopyroxene, olivine and magnetite.Apatite is¯uor-apatite, with rather homogeneous major element (measured by electron microprobe, EMP) and REE (measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The larger LREE partitioning in ET-1 is consistent with the more incompatible nature of these elements that usually allows them to fractionate into intraplate basic magmatic products such as those associated with the Mt. Etna volcanism (Busà et al 2002;Viccaro et al, 2006) and can be observed both in the labile and whole fractions. By contrast, the MREE fractionation in PA soils could be related to their larger Fe-oxyhydroxide and carbonate contents (Bau, 1999;Haley et al, 2004).…”
Section: Soilsmentioning
confidence: 60%
“…The larger LREE partitioning in ET-1 is consistent with the more incompatible nature of these elements that usually allows them to fractionate into intraplate basic magmatic products such as those associated with the Mt. Etna volcanism (Busà et al 2002;Viccaro et al, 2006) and can be observed both in the labile and whole fractions. By contrast, the MREE fractionation in PA soils could be related to their larger Fe-oxyhydroxide and carbonate contents (Bau, 1999;Haley et al, 2004).…”
Section: Soilsmentioning
confidence: 60%
“…3). The Tawau lavas can be divided 199 into four sub-groups (PP1 to PP4) for which, at any concentration of MgO which could indicate crystallisation of apatite, however, Semporna lavas are more mafic than 213 would be suitable for apatite saturation at these P 2 O 5 concentrations in basalt or alkali basalt 214 (DeLong and Chatelain, 1990; Busà et al, 2002). 215…”
Section: Techniques 160mentioning
confidence: 99%
“…Our study demonstrated that in the cross-section of Rasvumchorr deposit the concentrations of Sr, Ce, and La in apatite systematically increase with the increasing stratigraphic height (Figure 4). In the huge alkaline magmatic chamber of Etna (Italy) volcanic system, the content of REE in apatite also increases with the degree of differentiation [3]. The compositional evolution of the Khibiny apatite reflects the primary fractionation processes in the alkaline magma that differentiated from the bottom to the top of the magma chamber as a result of magmatic convection, coupled with the settling of minerals with different settling velocities.…”
Section: Genetic Problems Of the Khibiny Apatite Depositsmentioning
confidence: 99%
“…Apatite is a common accessory mineral and it has been extensively used to obtain significant genetic information [1][2][3][4]. This mineral is found in virtually all igneous rocks due to expanded crystallization fields.…”
Section: Introductionmentioning
confidence: 99%